Pengembangan Kertas Indikator pH Ramah Lingkungan yang Berasal dari Ekstrak Bunga Telang (Clitoria ternatea) - Ariwidiani, Ni Nyoman; Anulus, Ayu; Metriani, Putu Desy (Alpatih Harapan Semesta, 2024)
Acid-base indicator paper is a type of paper that changes color when exposed to an acid or base solution, used to distinguish the properties of a substance as either acidic or basic. Several studies have been conducted to find alternative plants that can be used as acid-base indicators.One of them is the butterfly pea flower. The need for practical and economical indicator testing tools prompted researchers to test indicator paper that is cheaper compared to litmus paper. The paper tested comes from commonly found paper in the surroundings, namely HVS paper, BC paper, and Whatman paper. Research objective: Creating Kerinlang, an innovative alternative paper for acid-base indicators using the Telang flower (Clitoria Ternatea). Research method: Maceration of Butterfly Pea Flower is carried out with a 70% ethanol solution to produce an extract from the butterfly pea flower (Clitoria ternatea). The ethanol extract of butterfly pea flower (Clitoria ternatea) was soaked using HVS paper, BC paper, and Whatman paper, then tested with acid-base test solutions to observe the resulting color changes as well as the structure and durability of the tested paper. Conclusion: Kerinlang can be used as an alternative pH indicator paper for butterfly pea flower (Clitoria ternatea) with Whatman paper as the medium, which produces the best color change, is durable, and inexpensive.